MODERN METHODS OF ANXIETY ASSESSMENT of RODENTS BY TESTS BASED ON UNCONDITIONal BEHAVIOR MODELS - A. Kh. Kade; S. V. Kravchenko; A. I. Trofimenko; P. P. Poliakov; A. S. Lipatova; E. I. Ananeva; K. Iu. Chaplygina; E. A. Uvarova; O. A. Tereschenko (Кубанский научный медицинский вестник, 2018)
Aim. The main aim of this research is to overview some main methods of anxiety assessment of animals by the behavioral tests based on the unconditional models. Animal models of anxiety disorders are actively used for studying their etiology and pathogenesis and for their treatment and prevention. This review describes some basic unconditional methods of anxiety disorders assessment in laboratory animals: open field test, light-dark box test / light-dark exploration box, elevated plus-maze and Suok test. The principles of conducting this test, regulated parameters and their link with anxiety-level are described.Conclusion. A modern researcher possesses different methods of modeling anxiety disorders in rodents. The tendency to an in-depth assessment of the behavioral reactions is noted. The use of the described models allows us to reveal and analyze the anxiolytic activity of new pharmacological drugs and non-pharmacological methods of pathological anxiety management. The most important aspect of performing this research is the correct matching of received data and normal and pathological human physiology features.